OPTIMIZATION OF ENERGY-POWER MODE IN IMPACT EXTRUSION OF RODS PRODUCTION WITH BUTT-END CLADDING - I. V. Kachanov (Nauka i Tehnika, 2008)
The paper proposes mathematical model for evaluation of energy expenditure for high-speed extrusion process of rods with butt-end cladding.The function dependence for determination of minimum cladding force has been obtained that is  necessary for formation of high-quality welding joint.